2010
DOI: 10.1093/gerona/glq152
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Midlife Physical Activity on Cognitive Function Among Older Adults: AGES—Reykjavik Study

Abstract: Midlife PA may contribute to maintenance of cognitive function and may reduce or delay the risk of late-life dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
133
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 158 publications
(150 citation statements)
references
References 36 publications
12
133
0
5
Order By: Relevance
“…The limitation of the relationship between physical activity and dementia/AD in the present investigation only to noncarriers of the APOEε4 allele is consistent with observations in the Cardiovascular Health Cognition Study (17) and the AGES Study (18). Previous studies have shown that APOEε4 carriers do not derive the same blood pressure and lipid benefits from physical activity as noncarriers (32,33).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The limitation of the relationship between physical activity and dementia/AD in the present investigation only to noncarriers of the APOEε4 allele is consistent with observations in the Cardiovascular Health Cognition Study (17) and the AGES Study (18). Previous studies have shown that APOEε4 carriers do not derive the same blood pressure and lipid benefits from physical activity as noncarriers (32,33).…”
Section: Discussionsupporting
confidence: 81%
“…The suggestion of diminishing returns with greater amounts of physical activity is also consistent with findings from two studies with follow-up of more than 20 years (3,18). Therefore, it is necessary for future studies to stratify by level of physical activity, or use nonlinear modeling, to accurately assess this relationship.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…There may even be an upper limit beyond which extensive physical activity may not yield any added benefit. A study examining physical activity and dementia did not find a significantly reduced risk for those participating in over 5 h per week of exercise (Chang et al 2010). Alternatively, the protective effect may be cumulative as higher levels of activity showed less cognitive decline in a study of women aged 70 years and older performing regular physical activity for 8 to 15 years (Weuve et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Case finding was based on a three-step procedure, previously described [10,11]. Dementia and MCI were diagnosed by a consensus conference following the criteria of the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition [12].…”
Section: Cognitive Status (Normal-mci-dementia)mentioning
confidence: 99%